ANALYSIS OF THE DEGRADABILITY OF AZO DYES AND MICROBES BIOPLASTICS FROM CELLULOSE Kappaphycus alvarezii - Zhaleha Zhaleha; Tri Widayati Putri; Awaluddin Awaluddin; Zul Khairiyah (Jurnal Riset Diwa Bahari (JRDB), 2026)
The increasing accumulation of non-biodegradable plastic waste has encouraged the development of environmentally friendly alternatives derived from renewable natural resources. One promising material is cellulose extracted from the red seaweed Kappaphycus alvarezii, which possesses favorable characteristics for bioplastic production. This study aimed to evaluate the degradability of azo dyes and microbial activity in bioplastics produced from K. alvarezii cellulose with different cellulose-to-cassava starch ratios. The research was conducted from July to October 2025 using five formulations: F1 (5:5), F2 (8:2), F3 (2:8), F4 (0:10), and F5 (10:0). Cellulose extraction was performed through alkaline and acid hydrolysis methods, while bioplastic films were produced through solution casting with glycerol as a plasticizer. Azo dye degradation was analyzed using UV–Visible spectrophotometry, whereas microbial activity was evaluated through Total Plate Count (TPC) analysis. The UV–Vis results revealed no characteristic absorption peaks of azo dyes in the 300–500 nm wavelength range, indicating the absence or successful degradation of azo chromophores in all formulations. Cellulose-rich formulations exhibited higher optical transparency and greater film homogeneity than starch-dominated formulations. TPC values ranged from 0 to 420 CFU g⁻¹ and remained substantially below the maximum limit established by SNI 7388:2009 (4,400 CFU g⁻¹), confirming excellent microbiological quality and product safety. Statistical analysis using the Kruskal–Wallis test showed no significant differences among formulations (p > 0.05). The combined findings demonstrate that cellulose-based bioplastics derived from Kappaphycus alvarezii possess good biodegradation potential, are free from detectable azo dye contamination, and maintain low microbial contamination levels. Therefore, these bioplastics have strong potential as sustainable alternatives to conventional petroleum-based plastics for food packaging, cosmetic packaging, and other environmentally sensitive applications